Anti-inflammatory Activity of Ointment in Water Soluble Base of Volatile Oil of Syzygium aromaticum with Variation Composition of Oleic acid and Propylene glycol as Enhancer - Dewi Rahmawati; Nining Sugihartini; Tedjo Yuwono (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: The dosage form of ointment clove essential oil in water-soluble base has proven efficacious as anti-inflammatory with eugenol as active substance. Further research to increase the penetration of eugenol in penetrating the skin layer needs to be done with the addition of enhancer. Purpose: To determine the anti-inflammatory activity of ointment base water soluble of clove essential oil with composition variation of oleic acid and propylene glycol as enhancers. Methods: The ointment was made using fusion method. Addition of enhancer composition refers to the system Simplex Lattice Design for Formula 1, Formula 2 and Formula 3 successively used: 100% oleic acid; 50% oleic acid: 50% propylene glycol; and 100% propylene glycol. The evaluation of anti-inflammatory activity was based on the parameters epidermal thickness, the number of inflammatory cells, and the number of cells that expressed cyclooxygenase-2 (COX-2). The anti-inflammatory tests used male mice strain BALB/C which was induced by croton oil. Results: The enhancer composition of oleic acid and propylene glycol affect the activity of ointment clove essential oil in water-soluble base. Conclusion: The increasing composition of propylene glycol improved anti-inflammatory activity of ointment.